ORCID and PIDs from scratch - Jefferies, N (Bodleian Libraries, University of Oxford, 2023)
ORCID (Open Researcher and Contributor ID) is a researcher-controlled persistent identifier that is being adopted by publishers, funders and other scholarly comms infrastructures. Its primary goal is to ensure that research outputs can be attributed correctly and unambiguously in the digital world. This workshop will begin with a presentation that explains what an ORCID is, how it works and how it fits in with the broader use of persistent identifiers (PID’s) in the academic sphere. This will be followed by a a hands-on session where we will take you through the process of acquiring an ORCID, linking it to your Oxford Single Sign On and updating your ORCID record with publciations or other material.